Use of the gastro-laryngeal tube in endoscopic retrograde cholangiopancreatography cases under sedation/analgesia - Daşkaya, Hayrettin; Uysal, Harun; Çiftçi, Taner; Baysal, Birol; İdin, Kadir and Karaaslan, Kazım (Turkish Journal of Gastroenterology, 2016)
Abstract Background/Aims: In this study, we aimed to analyze the effects of Gastro-Laryngeal Tube (GLT) use on intraoperative and postoperative hemodynamic parameters, comfort of the procedure, and patients’ satisfaction in endoscopic retrograde cholangiopancreatography (ERCP). Materials and Methods: A total of 80 patients between the ages of 20 and 75 years who were scheduled for elective ERCP were enrolled. The patients were randomly assigned to two groups: groups N and G. Those in group N underwent the procedure with sedation without any airway instruments and those in group G underwent procedure after sedation and airway management with GLT. Intraoperative and postoperative vital signs as well as the satisfaction of the patients were recorded. Results: The duration to esophageal visualization was found to be significantly higher in group N (16 s) than in group G (7 s) (p=0.001). The mean Visual Analogue Scale for Pain (VAS) was significantly higher in group G (1.85) than in group N (0.45) (p=0.016). Group G had higher endoscopist satisfaction scores than group N. The incidence of desaturation during ERCP was significantly higher in group N (60%) than in group G (0%) (p=0.000). Conclusion: In conclusion, ERCP should be performed under optimal conditions to avoid the occurrence of unwanted complications, such as aspiration-related disorders. Therefore, according to the structural properties of GLT, sedation anesthesia application with GLT in ERCP will be safer, more comfortable, and more effective.